CONTRIBUTIONS TO THE HISTORY OF BOTANY AND EXPLORATION IN MALAYSIA-7 - H. C. D. DE WIT (Research Center for Biology, 1951)
Barchewitz reached the islet of Leti,in the southwestern Moluccas,on September 2, 1714;he returned to Europe in September 1720, having represented the East India Company on Leti for six years.Like so many of his contemporaries he wrote a book on his life's adventures.This work appeared in 1730 and proved a success. A second, slightly enlarged, edition followed in 1751,entitled